Pengaruh Kecerdasan Emosional Terhadap Penyesuaian Diri pada Mahasiswa Tahun Pertama - Qonita Rohima; Rani Sagita; Muhammad Ikhwanurrahim; Syahidah Alifia; Shakira Ghaniya Irhamni; Nahrul Izza Mutiara Aldin; Aggio Malvino (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to determine the influence of emotional intelligence on self-adjustment among first-year Psychology students at Padang State University. Using a quantitative, correlational design with a survey method, data were collected from 82 students selected through purposive sampling. Two Likert-type scales were used: the emotional intelligence scale (42 items, reliability = 0.839) and the self-adjustment scale (40 items, reliability = 0.825). The data were normally distributed (p = 0.143 for emotional intelligence; p = 0.199 for self-adjustment) and showed a linear correlation (p = 0.000). Simple regression analysis revealed a significant influence of emotional intelligence on self-adjustment (p = 0.000; p < 0.05). The relationship was positive and unidirectional, with an R-square value of 0.514, indicating that emotional intelligence accounts for 51.4% of the variance in self-adjustment. The regression analysis also produced a constant (a) of 38.284 and a regression coefficient (b) of 0.685, demonstrating that higher emotional intelligence corresponds with better self-adjustment in students.